Influence of the hospitality industry on the development of the national economy - Zolotareva, Evelina; Nikitina, Tatyana (My University, 2023)
Індустрія гостинності є однією з найбільших і швидкозростаючих галузей у світі. Готельний бізнес робить значний внесок у валютні резерви країни та надає прямі та непрямі можливості працевлаштування широкому прошарку населення. Отже актуальним є дослідження впливу індустрії гостинності на розвиток національної економіки. The hospitality industry is one of the largest and fastest growing industries in the world. The hotel business makes a significant contribution to the country's foreign exchange reserves and provides direct and indirect employment opportunities to a wide segment of the population. Therefore, it is relevant to study the impact of the hospitality industry on the development of the national economy.
Keywords: кафедра готельно-ресторанної справи; індустрія гостинності; готельний бізнес; національна економіка; hospitality industry; hotel business; national economy